Genome-Wide CRISPR Screen Identifies Host Factors Required by Toxoplasma gondii Infection - Wu, Shui-Zhen; Wei, Hai-Xia; Jiang, Dan; Li, Sheng-Min; Zou, Wei-Hao; Peng, Hong-Juan (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii are obligate intracellular protoza, and due to their small genome and limited encoded proteins, they have to exploit host factors for entry, replication, and dissemination. Such host factors can be defined as host dependency factors (HDFs). Though HDFs are inessential for cell viability, they are critical for pathogen infection and potential ideal targets for therapeutic intervention. However, information about these HDFs required by T. gondii infection is highly deficient. In this study, the genes of human foreskin fibroblast (HFF) cells were comprehensively edited using the lentiviral CRISPR-Cas9-sgRNA library, and then the lentivirus-treated cells were infected with T. gondii at multiplication of infection 1 (MOI = 1) for 10 days to identify HDFs essential for T. gondii infection. The survival cells were harvested and sent for sgRNA sequencing. The sgRNA sequence matched genes or miRNAs were potential HDFs. Some cells in the lentivirus-treated group could survive longer than those in the untreated control group after T. gondii infection. From a pool of 19,050 human genes and 1864 human pri-miRNAs, 1193 potential HDFs were identified, including 1183 genes and 10 pri-miRNAs (corresponding with 17 mature miRNAs). Among them, 7 genes and 5 mature miRNAs were validated with siRNAs, miRNA inhibitors, and mimics, respectively. Bioinformatics analysis revealed that, among the 1183 genes, 53 potential HDFs were associated with regulation of host actin cytoskeleton and 23 potential HDFs coded immune negative regulators. This result indicated that actin dynamics were indispensable for T. gondii infection, and some host immune negative regulators may be involved in disarming host defenses. Our findings contribute to the current limited knowledge about host factors required by T. gondii infection and provide us with new targets for medication therapy and vaccine exploitation.